PENINGKATAN EFISIENSI DAN EFEKTIVITAS OPERASIONAL NELAYAN PADA PANTAI YANG CURAM DENGAN ALAT PEMINDAH PERAHU - Tanaya, IGNA; Suartika, Made; Okariawan, IDK (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2013)
Indonesia is known as an archipelago that has abundant marine resources, this should make Indonesia a wealthy and prosperous country. Unfortunately, these resources cannot be fully utilized because there is still a lack of support for technology and human resources in an effort to explore the existing marine resources. It is no wonder then many coastal communities are middle to lower living standards. Most of the fishermen have to pay people to help the process of shifting their boat, especially the fishermen on the steep coast so that it can reduce their revenue.This research aims to improve the operational productivity of fishermen on the steep coast by using an alternative concept, so that it reduces human labor as shifting assistant in the traditional shifting. Three alternative concepts has been designed to assist those shifting process, ie Tripod, Boat Train, and Boat Wheel. The designs was then selected to obtain the best concept. Concept selection was using the matrix assessment Analitycal Hierarchy Process (AHP) by assistance of data processing using Expert Choise 11 program furthermore method followed by using Pugh method to compare the boat shifting process between alternative concept and traditional shifting.Concept selection gives certain point for each concept, Tripod 0.3044 point, Boat Train 0.3998 point, and Boat Wheel 0.4385 point. It shows that boat wheel design selected as the best alternative concept. The comparison of total productivity between the best alternative concept and traditional shifting is 2.32 to 1.66. It means boat shifting process by using alternative concept design can be increase productivity counting 28%.